Hybrid Work Support Factors toward Work Life Balance by Employees of Power Plant Company in Thailand - Puttharuksa, Nartsuda; Luekitinan, Wannapa (Journal of MCU Phetchaburi Review, 2025)
This study aimed to investigate opinions on hybrid workplace support factors and the level of work-life balance, including the influence of hybrid workplace support factors on employees’ work-life balance. The research sample was 300 employees working in hybrid workplaces. The research instrument was a questionnaire, and the researcher collected data using an online questionnaire. A total of 245 completed questionnaires were received, resulting in a response rate of 79.29%. The data analysis employed frequency, percentage, mean, standard deviation, independent t-test, one-way ANOVA, and multiple regression analysis. The results found that employees had a high level of opinions on supporting hybrid workplaces factors in terms of policies and practices, work systems and technology, supervisors, and employee characteristics. Additionally, employees reported high levels of work-life balance. Further, different personal factors, such as gender, age, education level, job position, department, work experience, and office location, affected employees’ work-life balance. Moreover, the hybrid workplace support factors in terms of employee characteristics had a positive influence on employees’ work-life balance by 39%.